English – Indonesian Passive Sentences in Cookbook (e-Journal of Linguistics, 2020)
This research focuses on the English-Indonesian passivesentence in cookbook. The aim of this research is to find outhow the English passive sentence translated into Indonesianpassive one cookbook. The data source was taken fromEnglish cookbook entitled The Essential Book of Sauces &Dressings written by Lowery, et.al and published byPeriplus, Singapore and the translation into Indonesianentitled “Saus dan Dressing yang esensial” translated byHadyana P. and published by Periplus, Indonesia. Themethods of collecting data are observation anddocumentation. Scintific article tends to use passivesentence rather than active one. This is intended to show theproduct and disappear the doer. In doing the works, thetranslator translated English passive voice into Indonesianpassive voice in several ways. The results show in Englishcookbook found some passive constructions which aretranslated also into passive construction in TL. The passiveconstruction in English cookbook are in the form of presenttense (is/are + V past participle), modal passive (modal + be+ V past participle), present perfect tense (has + been + Vpast participle). The translation in Indonesian are translatedinto passive construction by using verbs added by prefix di-,active construction with active verbs, and verbs added byprefix ter-.
Keywords: English passive voice; Indonesian passive voice; Cookbook